Comparison of haemocytic parameters among flat oyster Ostrea edulis stocks with different susceptibility to bonamiosis and the Pacific oyster Crassostrea gigas - Comesana, Pilar; Casas, Sandra M.; Cao, Asuncion; Abollo, Elvira; Arzul, Isabelle; Morga, Benjamin; Villalba, Antonio (Journal of Invertebrate Pathology, 2012)
Farming of the flat oyster Ostrea edulis in Europe is severely constrained by the protozoan Bonamia ostreae. The introduction of the resistant species Crassostrea gigas has been a relief for the farmers, while the pilot programmes to select O. edulis strains resistant to bonamiosis performed in various countries can be seen as a promising strategy to minimise the effects of bonamiosis. However, the physiological bases of this differential susceptibility remain unknown. A search for an explanation of the intra and interspecific differences in oyster susceptibility to bonamiosis was accomplished by comparing some immune parameters among various O. edulis stocks and C gigas. On December 2003, naive and Bonamia-relatively resistant flat oysters from Ireland. Galician flat oysters and Pacific oysters C. gigas were deployed in a Galician area affected by bonamiosis; haemolymph samples were taken in February and May 2004. A new oyster deployment at the same place was carried out on June 2004 and haemolymph sampling was performed on April 2005. On November 2004, new sets of Irish flat oysters and C. gigas were deployed in Ireland and haemolymph sampling was performed in June 2005. Various haemocytic parameters were measured: total and differential haemocyte count, phagocytic ability, respiratory burst (superoxide anion [O-2(-)] and hydrogen peroxide [H2O2]) and nitric oxide [NO] production. The comparison of the parameters was carried out at 3 levels: (1) between O. edulis and C. gigas, (2) among O. edulis stocks with different susceptibility to bonamiosis, and (3) between Bonamia-infected and non infected O. edulis. In addition, haemocyte-B. ostreae in vitro encounters were performed to analyse interspecific differences in the haemocytic respiratory burst, using flow cytometry. Significant differences associated with total and differential haemocyte count, and respiratory burst between O. edulis and C. gigas were detected, which could be linked to differences in susceptibility to bonamiosis between both species. ...